Baseline study of household solid waste management practices among orang ulu community in sungai asap, belaga, sarawak toward carbon-neutral - Kulleh, Vitarich Julan; Manaf, Latifah Abd (Springer, 2023)
Developing countries’ dependency on landfills caused increasing greenhouse gasses emission. Sarawak, Malaysia is facing solid waste management issue due to landfill-dependency, especially in rural area. This study evaluated the household solid waste management practices in Sungai Asap, Belaga as a baseline to carbon-neutral. Quantification of segregated solid waste generated in Uma Belor, Uma Badang, and Uma Lahanan found to be lower than Sarawak’s rate at 0.43 kg/person/day, 0.47 kg/person/day, and 0.337 kg/person/day respectively. One-Way ANOVA revealed significant difference among food, plastic, and metal (p < 0.05) while insignificant difference among glass, paper, and other waste types (p > 0.05). Pearson correlation showed family income had moderately positive, statistically significant (r = 0.393, p < 0.001) while family size has low positive, statistically insignificant (r = 0.141, p > 0.05) relationship with waste generation. Interviews with villages’ representatives and Local Authorities revealed waste management practices, collection service inconsistency, and waste bins insufficiency were the main reasons for waste management issues. Therefore, this needed to be handled strictly to ensure sound household waste management practices. Finally, different approaches had to be implemented on the different types of waste to ensure holistic solutions can be established to achieve carbon-neutral community.